Protocolo NICHD : validação e capacitação em uma amostra de profissionais brasileiros - Hackbarth, Chayene (Universidade Federal de São Carlos, 2015)
This Master’s thesis is a compendium of three scientific texts. Each one describes different steps of the study in order to contribute to the validation of the NICHD protocol in Brazilian context. The first article describes a systematic international literature review regarding to the appropriate listening and strategies for investigation of child sexual violence, with special emphasis on NICHD Protocol (National Institute of Child Health and Human Development). This protocol is recognized by the international specialized literature as one of the most appropriate tools for structured interviews with children victims of violence. It appears as a structured instrument, providing superior information to those obtained by interviews with fewer open questions. The result of this review showed that NICHD protocol produce more precise answers compared to others, with more both detailed and rich reports and with more revelations. The second text produced was related to a pilot study conducted to evaluate a training course on the NICHD Protocol to Brazilian psychologists, with the purpose of analyzing the quality of information obtained in interviews with children in cases of suspected sexual abuse. The results indicated that interviews that included sexual abuse revelations presented both a satisfactory amount of open questions and forensic relevance detail, showing good quality information. Those findings suggest a future application of the protocol to a higher number of participants in order to compare the quality information obtained during the interview before and after the course. Finally, the last article evaluated a training about the NICHD protocol offered to 15 professionals (psychologists and social workers) of two Brazilian cities. The results suggest that after training, there was a significant increase in using open-ended questions during interviews, as well as significant increase rate in forensic relevance details regarding to direct questions. The participant’s evaluation was positive. Limitations founded refer to small number of participants during the training and consequently low quantity of interviews, as well as intrinsic problems to the Brazilian forensic context, which foreseeing direct and suggestive questions during children testimony.
Keywords: NICHD Protocol; forensic interviews; child sexual abuse; children testimony; Protocolo NICHD; entrevistas forenses; abuso sexual infantil; oitiva de crianças; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL